Answer:
(-8,7)
Step-by-step explanation:
5x+9y=23
-2x+y=23
Step 1. When looking at the equation you need to find out what method you must use and a good way to find out if you use subtraction is to look for a variable of 1
just like -2x+y=23 has the variable 1y
Step 2. solve for y in the second equation
-2x+y=23
+2x +2x
y=2x+23
Step 3. rewrite your equation
5x+9y=23
y=2x+23
Step 4. replace your y variable with the expression you just made
5x+9(2x+23)=23
Step 5. Distribute the 9 and solve
5x+18x+207=23
23x+207=23
23x=-184
x=-8
Step 6. enter your x value into the equation you solved in step one
y=2(-8)+23
y=-16+23
y=7
Step 7. determine if consistent or inconsistent
Because you have a x and y you have an consistent
...you can also graph it